Optoelectronic simulation properties of transparent conducting indium tin oxide for solar cell application - Isiyaku, Aliyu Kabiru; Ali, Ahmad Hadi; Ahmad, Rabiatul Adawiah; Bhari, Bibi Zulaika (Journal of Science and Technology, 2017)
The flexible and unique features of indium tin oxide (ITO) have continued to qualify this material for used in wide range of optoelectronic applications. Optical and electrical properties of indium tin oxide were investigated using a computer simulation (Matlab program). Derived models of ITO comprising transmission, resistivity and optical absorption were used to examine and validate the trend features of the ITO transparent conductive material. All the models parameters used in this study were within the limit range values of the material and have found to affect changes in the electronic and optical properties of indium tin oxide. Data obtained in this work were compared with the experimental findings. The attractive features of the results indicate that the models used can be further manipulated to extract other parameters such as reflectance and temperature dependent transmittance.